A study on the interaction of family function of parents of premature infants on home care preparation (早产儿父母家庭功能对家庭护理准备的交互作用研究) - JIANG Canhui (江灿慧); CHEN Yingfang (陈樱芳); YE Yanli (叶严丽) (中西医结合护理)
Objective To analyze the interaction between the family functions of the father and mother of premature infants and their preparation for home care, and provide reference for clinical intervention measures to improve home care preparation. Methods Convenience sampling was used to select 218 pairs of parents of premature infants in our hospital as the research subjects. General information questionnaire, family care index questionnaire, and home care preparation scale were used to investigate all research subjects. The actor-partner interdependence model (APIM) was used to explore the interaction between parental family function and home care preparation of the children. Results The premature infants of mother had higher home care readiness than fathers, and the difference was statistically significant (P＜0. 05), but there was no statistically significant difference in family function between the parents of premature infants (P＞0. 05). The main effect showed that both the father and mother's family functions had a positive predictive value for their own family care preparation (β father=0. 214, β mother=0. 311, both P＜0. 05). Object effects show that both father and mother's family functions had positive predictive value for each other's family care preparation (β father to mother=0. 162, β mother to father=0. 197, both P＜0. 05). Paired mode display: The impact of parental family functions on home care preparation was a dual mode, while the mother was a mixed mode. Conclusion There is an interactive effect between the family function of parents of premature infants and their preparation for home care. Targeted interventions should be developed from a holistic perspective to better improve the peritoneal home care preparation of infants. (目的 分析早产儿父亲和母亲家庭功能对家庭护理准备的交互作用, 为临床制定干预措施提升家庭护理准备提供参考依据。方法 采用便利抽样法选取医院早产儿父母218对作为研究对象, 采用一般资料问卷、家庭关怀度指数问卷、家庭护理准备量表对所有研究对象进行调查研究, 主客体互倚模型(APIM)探讨早产儿父母家庭功能和家庭护理准备的交互作用。结果 早产儿母亲家庭护理准备高于父亲, 差异有统计学意义(P＜0. 05), 但两者间家庭功能差异无统计学意义(P＞0. 05)。主体效应显示: 患儿父亲和母亲家庭功能均对自身家庭护理准备有正向预测价值(β父亲=0. 214, β母亲=0. 311, P＜0. 05)。客体效应显示: 父亲和母亲家庭功能对对方家庭护理准备均有正向预测价值(β父亲-母亲=0. 162, β母亲-父亲=0. 197, P＜0. 05)。成对模式显示: 父亲母家庭功能对家庭护理准备影响为对偶模式, 母亲为混合模式。结论 早产儿父母家庭功能对家庭护理准备存在交互作用, 临床干预时应该将两者看成一个整体并制定针对性干预措施, 更好地提高患儿父母家庭护理准备。)